Inclusão digital: estudo comparado de políticas públicas da Colômbia e do Brasil - Diana Alexandra Cubillos Vargas (2008)
The process of globalization and the struggle for world hegemony and its social impacts, related to the field of knowledge, require corporate citizens and their field of technical apparatus of information technology and communication (ICT) as a key element to the inclusion of countries in information society. The democratization of information through ICT, contributes to reducing the inequality and creates new opportunities for social growth, which passes to require the establishment of policiesor guidelines that guide the public on the use of networks and their content for knowledge and develop skills. In this scenario, the research chose describing two government programs as national policies for digital inclusion of the governments of Colombia and Brazil, with the intention of comparing their goals, the aspects of depth, the similarities, strengths and weaknesses of actions implemented, and thus establish, against the objectives and indicators used, a rough evaluation, because ifwe show that the implementation of programs and plans of successive digital inclusion, requires analyses on the politics of information implemented by the States of the developing countries.